Comparison Pan Evaporation Data with Global Land-surface Evaporation GLEAM in Java and Bali Island Indonesia - Trinah Wati; Ardhasena Sopaheluwakan; fatkhuroyan fatkhuroyan (Faculty of Geography, Universitas Gadjah Mada, 2018)
This paper evaluates the variability of pan evaporation (Epan) data in Java and Bali during 2003-2012 and compares to GLEAM (Global Land-surface Evaporation: the Amsterdam Methodology) data version v3.b namely actual evaporation (E) and potential evaporation (Ep) in the same period with statistical method. Gleam combines a wide range of remotely sensed observations to the estimation of terrestrial evaporation and root-zone soil moisture at a global scale (0.25-degree). The aim is to assess the accuracy of Gleam data by examining correlation, mean absolute error, Root mean square error and mean error between Epan and Gleam data in Java and Bali Island. The result shows the correlation between Epan with Ep Gleam is higher than Epan with E Gleam. Generally, the accuracy of Gleam data is a good performance to estimate the land evaporation in Java and Bali at annual and monthly scale. In daily scale, the correlation is less than 0.50 both between Epan with E Gleam and between Epan with Ep Gleam. In daily scale, the average errors ranging from 0.15 to 3.09 mm according to RMSE, MAE, and ME.The result of this study is essential in providing valuable recommendation for choosing alternative evaporation data in regional or local scale from satellite data.